Epic undertakings - World Sanskrit Conference 2003 : Helsinki, Finland); Goldman, Robert P.; Tokunaga, Muneo (Delhi : Motilal Banarsidass, 2009)
Papers presented at the 12th World Sanskrit Conference, held at Helsinki during 13-18 July 2003.
Sadrži bibliografske bilješke i kazalo
Sadrži i tesktove na sanskrtu
Keywords: sanskrtska književnost -- epika -- Ramayana - teorija književnosti -- Mahabharata - teorija književnosti; vedska književnost; zbornik radova